Penyebab Pergeseran Penggunaan Bahasa Jawa Krama oleh Kalangan Muda di Desa Banyudono - Rosana Ambarwati; Fitri Alfarisy; Sephia Marginingtiastuti; Lesen Ambarsari (Titian: Jurnal Ilmu Humaniora, 2022)
This study aims to explain the factors that cause a language shift of the Javanese Krama language by young people in Banyudono village. Javanese Krama is a local language used to show politeness by Javanese people. However, the usage of the Javanese Krama is now rarely used by young people. The usage of the Javanese Krama language as a communication language was replaced by another language, namely the Javanese Ngoko language or Bahasa Indonesia. For this reason, it is necessary to know what factors cause language shift in the use of the Javanese Krama language by young people in Banyudono village. The method used in this study is qualitative. The techniques used in data collection are participant observation techniques and questionnaires. The population is all young people in Banyudono village. The technique that used in sampling is purposive sampling. Based on the result of the study, several factors that were found that caused a language shift of the Javanese Krama language by young people in Banyudono village are: the lack of knowledge of the Javanese Krama language by young people and not getting used to the Javanese Krama language since childhood in the family. This research is expected to be a reference source for further research related to the language shifting of the Javanese Krama language. Keywords: language shift, Javanese Krama language, young people.